Dynamic Simulation Analysis on Axle Spline of High-Speed Train Gauge-Change System. (10th April 2021) - Bai, Jinyi; Wang, Wenjing; Zhou, Pingyu; Wang, Yuguang
Abstract : Spline couplings are widely used in transmission systems to transfer torque due to their higher load carrying capacity and better durability performance. Most researches are conducted under static and quasistatic loading cases; however, very little is known about their contact behavior and stress distribution under dynamic loading cases, especially as a key transmission component between wheel and axle. In this paper, a 3D dynamic contact and impact analysis model of the wheel-axle spline of high-speed train gauge-change system is employed in order to investigate the effect of driving velocity and assembling error and vibration on spline couplings. Three categories of loading cases are considered: (i) 0.3 m/s 2 driving rate representing quasistatic loading case; (ii) 0.5 m/s 2 driving rate representing normal loading case, and (iii) 1 m/s 2 driving rate representing exceptional loading case. Aside from this, influence of spline misalignment, including radial misalignment and circumferential misalignment, has been investigated under normal loading case. Numerical results for surface integral contact analysis conducted by LS-DYNA and MATLAB were presented and compared for the verification of the results.